Salvation and Globalization in the Early Jesuit Missions - Clossey, Luke (Cambridge University Press, 2013)
This is the first truly global study of the Society of Jesus’s early missions. Up to now historians have treated the early-modern Catholic missionary project as a disjointed collection of regional missions rather thanas a single world-encompassing example of religious globalization. Luke Clossey shows how the vast distances separating missions led to logistical problems of transportation and communication incompatible with traditional views of the Society as a tightly centralized military machine. In fact, connections unmediated by Rome sprung up between the missions throughout the seventeenth century. He follows trails of personnel, money, relics, and information between missions in seventeenth-century China, Germany, and Mexico and explores how Jesuits understood space and time and visualized universal mission and salvation. This pioneering study demonstrates that a global perspective is essential to understanding the Jesuits and will be required reading for historians of Catholicism and the early-modern world.